Membangun Desa Wisata Batik sebagai Daya Tarik Wisata - Ihsan Budi Santoso; T. Prasetyo Hadi Atmoko (Media Wisata, 2019)
This study aims to determine the promotion strategy of Jarum’s tourism village and to find out the obstacles it faces. This research uses descriptive qualitative to describe the promotion strategy and its obstacles. The data is collected by interview, observation and documentation. Based on the data obtained, the promotion strategy that has been carried out in the tourism village of Jarum has been relatively using internet/social media to introduce its products such as Facebook, WhatsApp, Instagram. The exhibition/event is also very helpful in promoting the products. In overcoming the existing obstacles, facilitation in the management of tourism villages is needed. Government or private assistance is expected to cover all of these obstacles, such as limited human resources, networks and the absence of intensive assistance